2021
DOI: 10.35848/1347-4065/abd29f
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dependence of dV CE/dt on turn-off characteristics with a 1200 V double-gate insulated gate bipolar transistor

Abstract: The double-gate drive is a remarkable gate control technique for dramatically reducing turn-off loss in Si-insulated gate bipolar transistors (IGBT) by increasing dV CE/dt. However, no detailed analysis of the difference of turn-off mechanism according to the difference in dV CE/dt between double-gate drive and conventional gate drive has been reported. The double-gate (DG) drive allows the dV CE/dt of IGBTs to increase beyond the maximum dV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Dual-gate IGBTs, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] which have two independent control gates, can further reduce E off by suppressing the stored carrier density in the n− drift region prior to the turn-off switching. We proposed an integrated time and space carrier controllable dual-gate HiGT (i-TASC 31) ) that has two different hole injection efficiency regions within one chip and demonstrated that the trade-off between V CEsat and E off can be greatly improved.…”
Section: Introductionmentioning
confidence: 99%
“…Dual-gate IGBTs, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] which have two independent control gates, can further reduce E off by suppressing the stored carrier density in the n− drift region prior to the turn-off switching. We proposed an integrated time and space carrier controllable dual-gate HiGT (i-TASC 31) ) that has two different hole injection efficiency regions within one chip and demonstrated that the trade-off between V CEsat and E off can be greatly improved.…”
Section: Introductionmentioning
confidence: 99%